Plan de negocio para la creación de chocolates para diabéticos endulzados con inulina de yacón - Rodríguez Rodríguez, Andrea Stephanía (2017)
Diabetes is a noninfectious disease that prevents the pancreas from producing insulin. This disease has become one of the leading causes of death. The percentage of adults with diabetes in the world has increased from 4.7% to 8.5% between 1980 and 2014 (WHO, 2016). In Ecuador, diabetes in people aged 10 to 59 is 2.7% (INEC, 2014). Poor diet, obesity, family history and lack of exercise can trigger this disease (American Diabetes Association, 2014). The growing trend towards healthier habits, reflects a great opportunity for the "GoYac" project. The project deals with the production and sale of chocolates for diabetic people sweetened with yacon inulin. Yacon is a tuber that grows in the Andean zone, whose taste is sweet. Unlike most tubers that store carbohydrates in starch form, yacon stores FOS. FOS is a type of sugar that provides less calories to the body, does not raise blood glucose (Seminario, Valderrama and Manrique, 2014, p.7), promotes the growth and activity of beneficial bacteria (Roberts, O'Brien And Subak, 2003), and helps prevent cardiovascular diseases (López, 2007). The consumption is considered benefic. Especially for diabetic people. The goal of this plan is to give diabetic people the opportunity to consume a chocolate of great flavor, which at the same time contributes to their health. The project shows losses in the first year, because the production in the first months does not increase and the expenses are not recovered by the level of sales. This situation changes in year 2. A profit of $ 8,125 is achieved. As of this year there is a growing demand for chocolate and profit in year 5 increases to $ 37,929. The project has a positive NPV and a 25% IRR, which makes it attractive for future investors.